2013
DOI: 10.1016/j.molcel.2013.01.002
|View full text |Cite|
|
Sign up to set email alerts
|

RIF1 Is Essential for 53BP1-Dependent Nonhomologous End Joining and Suppression of DNA Double-Strand Break Resection

Abstract: SummaryThe appropriate execution of DNA double-strand break (DSB) repair is critical for genome stability and tumor avoidance. 53BP1 and BRCA1 directly influence DSB repair pathway choice by regulating 5′ end resection, but how this is achieved remains uncertain. Here we report that Rif1−/− mice are severely compromised for 53BP1-dependent class switch recombination (CSR) and fusion of dysfunctional telomeres. The inappropriate accumulation of RIF1 at DSBs in S phase is antagonized by BRCA1, and deletion of Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
596
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(668 citation statements)
references
References 56 publications
44
596
4
3
Order By: Relevance
“…Accumulated evidence suggests that 53BP1 is a key downstream effector in the ATM-dependent pathway and could be phosphorylated by ATM and CHK2 (Anderson et al 2001;Rappold et al 2001;Ward et al 2003). Phosphorylated 53BP1 is known to regulate its functional partners to govern the transient G2/M checkpoint and DNA damage repair (DiTullio et al 2002;Fernandez-Capetillo et al 2002;Callen et al 2013;Chapman et al 2013), which is consistent with our observations. Moreover, the PARdependent early ATM activation controls the transient G2/M checkpoint, which plays an important role in maintaining genomic stability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accumulated evidence suggests that 53BP1 is a key downstream effector in the ATM-dependent pathway and could be phosphorylated by ATM and CHK2 (Anderson et al 2001;Rappold et al 2001;Ward et al 2003). Phosphorylated 53BP1 is known to regulate its functional partners to govern the transient G2/M checkpoint and DNA damage repair (DiTullio et al 2002;Fernandez-Capetillo et al 2002;Callen et al 2013;Chapman et al 2013), which is consistent with our observations. Moreover, the PARdependent early ATM activation controls the transient G2/M checkpoint, which plays an important role in maintaining genomic stability.…”
Section: Discussionsupporting
confidence: 92%
“…During DNA damage response, 53BP1 is a key downstream effector of the ATM pathway (Anderson et al 2001;Rappold et al 2001;Ward et al 2003). Accumulated evidence suggests that ATM-dependent 53BP1 phosphorylation activates both the G2/M checkpoint and DNA damage repair (DiTullio et al 2002;Fernandez-Capetillo et al 2002;Callen et al 2013;Chapman et al 2013). Thus, we asked whether PAR regulates the ATM-dependent 53BP1 phosphorylation.…”
Section: Computational Analysis Of the Par-binding Pockets In The Fhamentioning
confidence: 99%
“…Similarly, elevated levels of Rif1 were found in breast cancer and teratocarcinomas (Wang et al ., 2009; Li et al ., 2015). Since mammalian Rif1 participates in suppressing the HDR repair pathway in the G1 phase (Chapman et al ., 2013; Di Virgilio et al ., 2013; Escribano‐Díaz et al ., 2013; Zimmermann et al ., 2013), it was suggested that too much Rif1 drives illicit and error‐prone DSB repair, which alters the genome. However, our study shows that Rif1 can drive genomic instability in the absence of DSB repair.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that 53BP1 inhibits resection, but that BRCA1 antagonizes 53BP1, allowing the nucleolytic processing of DNA ends in S phase (Bunting et al, 2010;Chapman et al, 2012). Furthermore PTIP and RIF1, both of which act downstream of 53BP1, inhibit BRCA1-associated DNA metabolism (Callen et al, 2013;Chapman et al, 2013;EscribanoDíaz et al, 2013;Feng et al, 2013;Zimmermann et al, 2013). Nevertheless, the mediators of resection in BRCA1/53BP1, BRCA1/PTIP, and BRCA1/RIF double-deficient cells have not been identified.…”
Section: Spontaneous and Parpi-induced Genome Instability In Ctip-defmentioning
confidence: 99%